(untitled) (CIPEEX, 2026)
BACKGROUND: Spirituality is understood as the search for meaning and purpose in life, which may or may not involve religion, and has been associated with the promotion of well-being. Health students, particularly those in Physical Therapy, face emotional, academic, and socioeconomic burdens that make them vulnerable to mental disorders. In this context, spirituality may serve as a coping resource. OBJECTIVE: To interpret the academic reality of Physical Therapy students at UniEVANGÉLICA – Anápolis regarding mental health and to analyze the influence of spirituality in this setting. METHODS: A descriptive, cross-sectional, and quantitative study was conducted with a sample of 43 Physical Therapy students from the 1st, 4th, and 8th semesters. Validated scales were applied through Google Forms. Statistical analysis was performed using SPSS, with significance set at p<0.05. RESULTS: Spirituality was predominant: 79% of students presented high spirituality (SSRS), and 72% reported high or very high spiritual perception (WHOQOL-SRPB). However, 74.4% indicated only moderate spiritual well-being (FACIT-SP12). Regarding mental health, 93% showed anxiety (69.8% extremely severe), 79% depression (48% severe or extremely severe), and 65% stress (37.2% severe). A family income of up to three minimum wages was reported by 51.2%, and 55.8% of students worked, factors associated with emotional overload. CONCLUSION: Spirituality remained constant throughout the undergraduate course and represented an important emotional support resource but was insufficient to prevent symptoms of anxiety, depression, and stress. The moderate level of spiritual well-being suggests that the practical experience of spirituality has a greater impact on mental health than mere spiritual perception. Socioeconomic aspects also significantly contribute to the psychological distress of these students.